2020
DOI: 10.1002/cphc.202000198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Upconverting Nanoplatform for Luminescent Thermometry from Ambient to Cryogenic Temperature

Abstract: Precise assessment of temperature is crucial in many physical, technological, and biological applications where optical thermometry has attracted considerable attention primarily due to fast response, contactless measurement route, and electromagnetic passivity. Rare‐earth‐doped thermographic phosphors that rely on ratiometric sensing are very efficient near and above room temperature. However, being dependent on the thermally‐assisted migration of carriers to higher excited states, they are largely limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…To construct ratiometric UCL nanoprobes, the ratio of dual-UCL peak intensities (UCL 1 , UCL 2 ) at respective wavelengths is used as signal output (UCL 1 /UCL 2 ) to establish a well-plotted (typically linear) func-Scheme 3 Schematic diagram of this present review focusing on the construction of UCL ratiometric nanoprobes for sensing, imaging and phototherapeutics applications. 36 LiYF 4 :20Yb 3+ /1Ho 3+ micro-octahedrons, 39 NaGdF 4 :Yb 3+ /Er 3+ microcrystals, 40 NaYF 4 :Er 3+ /Yb 3+ microspheres, 45 NaYF 4 :Er 3+ microcrystals, 54 NaY(Lu)F 4 :Yb 3+ /Mn 2+ nanocrystals, 87 etc. (c) Core@shell structural systems Lanthanide-doped Bi 2 SiO 5 @SiO 2 , 37 Bi 2 SiO 5 :Yb 3+ /Tm 3+ @SiO 2 , 38 Yb/Er@Yb/Nd, 41 Yb 3+ -sensitized Tm 3+doped GdVO 4 @SiO 2 , 68 NaYF 4 :Yb 3+ /Tm 3+ @NaYF 4 :Yb 3+ /Nd 3+ , 79 TPAMC-UCNPs@PEG, 102 UCNPs-Cy787 dyes@PC, 110 Ce 3+ -doped LiYF 4 :Yb 3+ /Ho 3+ @LiYF 4 , 126 UCNPs@PDA, 155 etc.…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
See 3 more Smart Citations
“…To construct ratiometric UCL nanoprobes, the ratio of dual-UCL peak intensities (UCL 1 , UCL 2 ) at respective wavelengths is used as signal output (UCL 1 /UCL 2 ) to establish a well-plotted (typically linear) func-Scheme 3 Schematic diagram of this present review focusing on the construction of UCL ratiometric nanoprobes for sensing, imaging and phototherapeutics applications. 36 LiYF 4 :20Yb 3+ /1Ho 3+ micro-octahedrons, 39 NaGdF 4 :Yb 3+ /Er 3+ microcrystals, 40 NaYF 4 :Er 3+ /Yb 3+ microspheres, 45 NaYF 4 :Er 3+ microcrystals, 54 NaY(Lu)F 4 :Yb 3+ /Mn 2+ nanocrystals, 87 etc. (c) Core@shell structural systems Lanthanide-doped Bi 2 SiO 5 @SiO 2 , 37 Bi 2 SiO 5 :Yb 3+ /Tm 3+ @SiO 2 , 38 Yb/Er@Yb/Nd, 41 Yb 3+ -sensitized Tm 3+doped GdVO 4 @SiO 2 , 68 NaYF 4 :Yb 3+ /Tm 3+ @NaYF 4 :Yb 3+ /Nd 3+ , 79 TPAMC-UCNPs@PEG, 102 UCNPs-Cy787 dyes@PC, 110 Ce 3+ -doped LiYF 4 :Yb 3+ /Ho 3+ @LiYF 4 , 126 UCNPs@PDA, 155 etc.…”
Section: Ratiometric Dual-signal Modes Of Ratiometric Ucl Nanoprobesmentioning
confidence: 99%
“…As summarized in Table 1, previous studies have largely reported various types of ratiometric UCL nanoprobes for temperature sensing. [168][169][170][171][172][173][174][175][176]193,194 Most of the nanoprobe systems consist of lanthanide-doped UCNPs, other upconverting luminescent inorganic materials, 29,36,40,43,45,47,48,54,[56][57][58][59][60][61]65,[73][74][75][76] and the derivatives with functional modifications, including the core@shell, 37,38,41,68,72,78,79 hollow/porous, 38 complexes, 46,49,51 hybrid, 32,52 mixture, 33,35 assembly, 34,55 or engineering structures.…”
Section: Sensing Of Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Cryogenics, a branch of physics that could cause intriguing changes in the properties of matter, play an important role in aerospace, biological engineering, infrared detectors, and energy technology, such as cryogenics can reduce the thermal noise to obtain reliable signals, decrease the reaction rate to capture the details of the reaction process in chemical research, and can be used for the simulation requirements of space exploration equipment. These fields require precise control of the appropriate temperature to meet different application requirements, where the cryogenic sensor is a fundamental measurement that can accurately reflect temperature changes in cryogenic environments. Conventional cryogenic thermometer generally require physical contact and thermal transmission, which are not suitable in many situations due to the limitation of spatial resolution, sensitivity and accuracy of detection . Efforts based on upconversion (UC) luminescence can provide a noncontact temperature measurement method, exhibiting fast response speed, high spatial resolution, and wide measurement range, which could provide the possibility for designing reliable cryogenic sensors owing to the diversification thermal response mechanisms of rare earth ions. Most UC optical temperature sensing is generally derived from the thermally coupled levels of rare earth ions, where the energy gap (200–2000 cm –1 ) of the particular rare earth ions enables temperature-induced population redistribution of related energy levels, following the Boltzmann-type distribution. However, these temperature sensors based on the thermally coupled energy levels are ineffective in ultralow temperature environments as they require strong thermal activation to populate the thermalized state from the lower thermal level …”
Section: Introductionmentioning
confidence: 99%